9 P62 deficiency protects against cerebral ischaemia in insulin resistant mice. (December 2018) - ,; Farrell-Dillon, Keith; Fraser, Paul; Mann, Giovanni; Chapple, Sarah
Abstract : Introduction and aim: Diabetic patients have poorer outcomes following ischaemic stroke. In rodents, similar findings are reported, with Type 1 and 2 diabetic rodents demonstrating increased infarct volume and worsened post-stroke recovery, which correlate with markers of autophagy overactivation post-ischaemia. p62 is a selective adaptor protein for autophagy, with mice lacking p62 (p62 KO) known to develop obesity-linked insulin resistance in adulthood and have supressed autophagic flux. To ascertain whether p62 is associated with ischaemic stroke pathophysiology, we evaluated post-stroke infarct volume and functional recovery in wild type (WT) vs p62 KO mice. Methods: All procedures were performed in male 8–9 week old C57BL/6 mice in accordance with the ARRIVE guidelines and Home Office regulatory approval. Transient focal ischaemia was induced by middle cerebral artery occlusion (MCAo) for 1 hour followed by reperfusion for 72 hour. Adhesive removal and open field assays were conducted daily 3 days prior to and 72 hour post-stroke to assess sensorimotor and motor function. Mice were then euthanised and brains perfused-fixed to obtain 10 µm sections every 1 mm relative to bregma. Infarct volume and astrocytosis were quantified using nissl staining and GFAP immunofluorescence, respectively. Data were analysed by unpaired student's t-test or 2-way ANOVA and Bonferroni post-hoc test as appropriate. Results: Infarct volume assessed by nissl staining showed a significant (p<0.01) reduction in p62 KO vs WT mice (16±3 vs. 30%±1% brain volume, respectively). Proliferation and activation of astrocytes assessed by GFAP staining was found to be reduced in the peri-infarct border in p62 KO vs WT mice (p<0.05). Furthermore, p62 KO showed marked improvements in post-reperfusion functional recovery. Reduced motor function was observed in WT mice, with a ˜70% reduction in max speed and total displacement vs baseline observed 72 hour post-reperfusion (p<0.01). No such impairments were reported in p62 KO mice. Similarly, sensorimotor function was impaired in WT mice post-reperfusion, with an increase in adhesive removal time in the affected (227±32 vs 29±9 ms at baseline, p<0.001) and unaffected (73±23 vs 16±3 ms at baseline, p<0.05) paw. p62 KO mice were protected, with adhesive removal times in the affected (51±44 vs 28±7 ms at baseline, p<0.05) and unaffected (61±39 vs baseline 28±7 ms at baseline) paws substantially improved when compared to WT mice at 72 hour. Conclusions: Our findings show that p62 KO mice are protected from cerebral ischaemia. This protection persists despite p62 KO mice being glucose intolerant, suggesting that p62 may be a meaningful therapeutic target even in comorbid diabetic populations. Further studies are needed to ascertain whether short-term functional recovery afforded by p62 deficiency persists long-term.